2017
DOI: 10.1038/s41598-017-06969-4
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of hesperidin in NMDA-induced retinal injury acts by suppressing oxidative stress and excessive calpain activation

Abstract: We found that hesperidin, a plant-derived bioflavonoid, may be a candidate agent for neuroprotective treatment in the retina, after screening 41 materials for anti-oxidative properties in a primary retinal cell culture under oxidative stress. We found that the intravitreal injection of hesperidin in mice prevented reductions in markers of the retinal ganglion cells (RGCs) and RGC death after N-methyl-D-aspartate (NMDA)-induced excitotoxicity. Hesperidin treatment also reduced calpain activation, reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 69 publications
2
61
0
Order By: Relevance
“…Since the doses administered to induce retinal excitotoxicity injury vary according to the literature used [17,[36][37][38][39][40][41], a series of experiments were performed to determine the ideal dose of joint administration of KA and NMDA in our model. Initially, in a series of mice (n = 3-4), different individual concentrations of NMDA (10, 30 and 100 mM) and KA (5, 10 and 20 mM) were administered by intraocular injection (see above), and the density of surviving RGC was estimated.…”
Section: Dose Estimation Of Excitotoxic Agentsmentioning
confidence: 99%
“…Since the doses administered to induce retinal excitotoxicity injury vary according to the literature used [17,[36][37][38][39][40][41], a series of experiments were performed to determine the ideal dose of joint administration of KA and NMDA in our model. Initially, in a series of mice (n = 3-4), different individual concentrations of NMDA (10, 30 and 100 mM) and KA (5, 10 and 20 mM) were administered by intraocular injection (see above), and the density of surviving RGC was estimated.…”
Section: Dose Estimation Of Excitotoxic Agentsmentioning
confidence: 99%
“…Harris Here, we gave a daily dietary antioxidant supplement over 8 weeks to patients with cataract and glaucoma. The supplement was developed and rst reported by Maekawa et al, who identi ed the components of the supplement through screening, and found that it had a neuroprotective effect in a mouse glaucoma model [22]. We believe that the ndings reported here will shed light on the potential of new treatments for cataract and glaucoma based on antioxidant supplementation.…”
Section: Introductionmentioning
confidence: 56%
“…A 2-lL NMDA solution diluted with PBS (15 mM) was injected into the vitreous cavity, as previously described. 24,25 In the controls that received NMDA injection, the same volume (2 lL) of PBS was injected. Vinblastine administration was also performed as described previously.…”
Section: Administration Of N-methyl-d-aspartate (Nmda) and Vinblastinementioning
confidence: 99%
“…Transcriptional gene expression analysis was performed as previously described. 25 Briefly, retinal total RNA was isolated with a purification kit (miRNeasy Mini Kit; Qiagen, Inc., Hilden, Germany), and cDNA was synthesized with reverse transcriptase (SuperScript III; Life Technologies, Inc., Carlsbad, CA, USA). Quantitative PCR (qPCR) was performed on a realtime PCR system (7500 Fast Real-Time PCR System; Life Technologies, Inc.) using a universal master mix (TaqMan Fast Universal PCR Master Mix; Life Technologies, Inc.).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation